Agglomerasi Industri : Industrialisasi Koridor Utara dan Selatan di Jawa Timur - Lustina Fajar Prastiwi; Kukuh Arisetyawan (EcceS (Economics, Social, and Development Studies), 2022)
Industrial agglomeration is the most prominent geographical feature of economic activity. East Java is one of the richest provinces in Indonesia that have north - south corridor industry agglomeration. In the northern region, it includes the City of Surabaya, Sidoarjo Regency, Pasuruan Regency, Mojokerto Regency, Gresik Regency, and Tuban Regency. The southern region includes Malang City, Malang Regency, and Kediri City. This study aims to discover whether industrial agglomeration is the key for region development and economic growth, especially on the East Java’s north-south corridor.This study also find the absorption of labor in each region as a result of industrial agglomeration in the northern and southern regions. This study used Location Quotion (LQ) and Shiftshare analysis to be able to represent the occurrence of industrial centralization in the northern and southern corridors of East Java in the period 2011 – 2019. The results analysis show that most of the sectors that form the basis of districts/cities in the north-south corridor generally excel in the industrial, trade, and service sectors. The absorption of labor in several industrial areas in East Java in the northern and southern corridors is also required by the completeness of regional infrastructure. The implications of the research is at the sectoral level cannot yet be described in depth on the performance of other sub-sectors in these economic activities, nor can they be fully developed because there are many factors that influence the development of a region.